Pyrohydraulic traits: the role of hydraulic segmentation as a hydraulic fuse in resisting fires - Bloy, Shonese Thora (Department of Biological Sciences, 2022)
Fire is known to kill trees, but the mechanisms underlying plant death and survival remain unclear. The central claim of the hydraulic death hypothesis (HDH) is that xylem embolism may kill plants by preventing tissues that survive fires from remaining hydrated and has been suggested to explain rapid post-fire mortality. A corollary of the HDH is that it would be beneficial for plants to invest in a suite of traits, ‘pyrohydraulic' traits, that may prevent embolism because this could aid post-fire survival. It was hypothesized that 1) the most distal parts along the branch of a fire-tolerant tree species, Eucalyptus cladocalyx, will act as a hydraulic fuse post-fire, in contrast to a fire sensitive species, Kiggelaria africana, where the hydraulic fuse post-fire would not be exhibited, and 2) the mechanism for this hydraulic fuse was vulnerability segmentation. A xylem conductance experiment post heat-plume (Chapter 2) and a vulnerability experiment (Chapter 3) were conducted on branches from both species. I predicted that 1) embolism would be localized to the distal parts of a branch for E. cladocalyx but not K. africana 2) non-suberized tissue of the distal tissue parts of E. cladocalyx branches will be more vulnerable to embolism than the suberized tissue, but K. africana would not exhibit this differentiation. Results indicate that embolism was localized to the most distal parts of a branch in E. cladocalyx, as well as that the non-suberized tissue was more vulnerable to embolism. E. cladocalyx suffered a 19% loss of conductance, while K. africana suffered a much greater 68% loss of conductance after heating. The P50 values of the non-suberized and suberized tissue sections were statistically similar in both species, but the P12 values differed between the sections for E. cladocalyx. E. cladocalyx was shown to be more vulnerable to embolism than K. africana. These results indicate that developing tissue of E. cladocalyx is more vulnerable to heat-plume induced embolism than developed stem tissue, consistent with the hypothesis that vulnerability segmentation is a pyrohydraulic trait. Therefore, the most distal parts of a E. cladocalyx branch acts as a hydraulic fuse and contributes to post-fire recovery. The phenomenon may be used by other fire-tolerant species as a strategy to survive post-fire, thereby enabling them to endure a fire and recover through protecting their hydraulic continuum.